2004
DOI: 10.1080/01431160412331291170
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing and GIS for detecting changes in the aquatic vegetation of a rehabilitated lake

Abstract: Remote sensing and geographical information system (GIS) methods combined with ground estimations were used to assess the effects of rehabilitation on the aquatic vegetation of a shallow, eutrophic lake in Finland. Aerial photograph interpretation was used to study the distribution of aquatic vegetation before (1953, 1996) and after (2001) rehabilitation in 1997. A digital elevation model was derived to relate the change in the aquatic vegetation to water depth. In addition, changes in the biomass of the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…UAS-technology is also especially favourable for monitoring purposes with short and/or user-defined repetition intervals. Our automated classification approach for water versus vegetation and at the growth-form level is highly applicable in lake and river management [53] and aquatic plant control, such as in evaluation of rehabilitation measures [54]. Valta-Hulkkonen et al [55] also found that a lake's degree of colonisation by helophytes and nymphaeids detected by remote sensing was positively correlated with the nutrient content in the water.…”
Section: Discussionmentioning
confidence: 91%
“…UAS-technology is also especially favourable for monitoring purposes with short and/or user-defined repetition intervals. Our automated classification approach for water versus vegetation and at the growth-form level is highly applicable in lake and river management [53] and aquatic plant control, such as in evaluation of rehabilitation measures [54]. Valta-Hulkkonen et al [55] also found that a lake's degree of colonisation by helophytes and nymphaeids detected by remote sensing was positively correlated with the nutrient content in the water.…”
Section: Discussionmentioning
confidence: 91%
“…Remote sensing can be used to map vegetation patch patterns with extended spatial and temporal coverage and thus has the potential to greatly improve our understanding of vegetation pattern dynamics in arid and semi-arid landscapes [ 21 , 24 ]. Aerial photographs are mostly used to study vegetation patch dynamics because of the higher spatial resolution, little affected by weather and longer historical archiving than satellite images [ 25 ]. Frenkel and Boss [ 26 ] monitored the establishment and exponential spread of distinctive circular Spartina patens patches on Cox Island, Canada, using sequential aerial photographs from 1939 to 1981.…”
Section: Introductionmentioning
confidence: 99%
“…In Lake Luupuvesi (central Finland) the extent of macrophytes increased from 96 ha in 1953 to 355 ha in 1996 (Valta-Hulkkonen et al 2004). However, the comparison of aerial photographs from the periods of 1947-1963 and 1996-2000 (Brižs 2011).…”
mentioning
confidence: 99%